PENGEMBANGAN DAN VALIDASI METODE SPEKTROFOTOMETRI UV-VIS DENGAN PEREAKSI PERMANGANAT UNTUK PENENTUAN KADAR ASAM MEFENAMAT DALAM SEDIAAN KAPSUL DAN TABLET - Amelia Chang, Ribka
Careful supervision of quality controls for drugs were done in order to ensure the quality and safety using methods that have been validated. Mefenamic acid is a commonly used drug in the market and is available in many dosage forms such as capsule, tablet, and suspension. In this study, a UV- Vis spectrophotometric method to measure the concentration of mefenamic acid by taking advantage of redox reaction with potassium permanganate is developed and validated. Absorbance measurement on the end product of mefenamic acid reaction, which is potassium permanganate was done on the maximum absorbance length 525 nm dan 545 nm. In this study, optimization of composition of reagent solution, heating condition, and concentration of mefenamic acid was carried out. This method is validated by measuring specificity, linearity, limit of detection, limit of qualification, accuracy, and precision. This method is proven to have good specificity and resulted in a linear relationship between absorbance and mefenamic acid concentration at 10-35 mg/L with coefficient correlation value (r) at 0,999 and linear regression coefficient variance (Vxo) at 1,38% for 525 nm, while coefficient correlation value (r) at 0,999 and linear regression coefficient variance at 1,28% for 545 nm. The limit of detection (LOD) and limit of qualification (LOQ) is measured statistically from the calibration curve, with 1,6 mg/L and 5,3 mg/L for 525 nm and 1,5 mg/L and 5,1 mg/L for 545 nm respectively. The percentage of recovery from the accuracy test was 99,7-99,9% for 525 nm and 99,5-101,1% for 545 nm. The percentage of relative standard deviation from the precision test on the same day (intraday) is in the range of 2% for 525 nm and 1,1% for 545 nm, while on different day (interday) in around 1,8% for 525 nm and 2% for 545 nm. Based on this study, a validated analytical method has been developed for determination of mefenamic acid in capsules and tablets.